PENGARUH UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Efriyenti, Dian; Azmiana , Risca; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2024)
Public financial case involving manipulation of financial reports by PT. Lippo proves that the practice of manipulation has not resolved the problems experienced, due to a lack of supervision from the commissioner, so that the government in Indonesia has made a bailout. This financial manipulation occurs due to weak implementation of corporate governance. The main characteristic of such activities is the lack of self-interested actions on the part of company managers. Small companies carry out more earnings management practices than large companies. This is because small companies tend to want to show the condition of a company that is performing well so that investors invest their capital in the company. Large companies can manage risks related to politics, so large companies tend to increase fiscal profits to increase external funds. The aim of this research is to analyze the influence of company size on earnings management, to analyze the influence of Good Corporate Governance on earnings management, to analyze the influence of company size and Good Corporate Governance on earnings management. The total registered population is 48 mining companies. The results of data processing show that company size and Good Corporate Governance influence earnings management both partially and simultaneously.